Simplify:(ab + bc)2 - 2ab2c
Simplify:(m2 - n2m)2 + 2m3n2
Show that(3x + 7)2 -84x = (3x -7)2
Show that (9p - 5 q)2 + 180pq = (9p + 5q)2
Show that             Â
Show that (4pq + 3q)2 - (4pq - 3q)2 = 48pq2 Â Â Â Â Â Â Â Â Â Â Â Â
Show that (a - b) (a +b) + (b - c) (b + c) + (c - a) (c + a) = 0Â Â Â Â Â Â Â Â Â
Using identities, evaluate:712
Using identities, evaluate:992Â
We have 100 - 1 = 99
∴    (99)2  = (100 - 1)2               = (100)2 - 2(100)(1) + (1)2               = 10000 - 200 + 1              = 9801
Using identities, evaluate:1022 Â